Mémoires d'Hyppolite Clairon, et réflexions sur l'art dramatique / publiés par elle-même. - Clairon, Mlle., 1723-1803. (Tufts University. Tisch Library., 2016)
1 online resource (2 preliminary leaves, ii, 360 pages); With half-title.; Includes index.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Binding: Tufts print Special Collections copy: Bound in contemporary tree calf significantly worn, red lettering piece to spine, all edges marbled.